Electromagnetic Interference from Swimming Pool Generator Current Causing Inappropriate ICD Discharges - Edward Samuel Roberto; Thein Tun Aung; Atif Hassan; Abdul Wase (Case Reports in Cardiology)
Electromagnetic interference (EMI) includes any electromagnetic field signal that can be detected by device circuitry, with potentially serious consequences: incorrect sensing, pacing, device mode switching, and defibrillation. This is a unique case of extracardiac EMI by alternating current leakage from a submerged motor used to recycle chlorinated water, resulting in false rhythm detection and inappropriate ICD discharge. A 31-year-old female with arrhythmogenic right ventricular cardiomyopathy and Medtronic dual-chamber ICD placement presented after several inappropriate ICD shocks at the public swimming pool. Patient had never received prior shocks and device was appropriate at all regular follow-ups. Intracardiac electrograms revealed unique, high-frequency signals at exactly 120 msec suggestive of EMI from a strong external source of alternating current. Electrical artifact was incorrectly sensed as a ventricular arrhythmia which resulted in discharge. ICD parameters including sensing, pacing thresholds, and impedance were all normal suggesting against device malfunction. With device failure and intracardiac sources excluded, EMI was therefore strongly suspected. Avoidance of EMI source brought complete resolution with no further inappropriate shocks. After exclusion of intracardiac interference, device malfunction, and abnormal settings, extracardiac etiologies such as EMI must be thoughtfully considered and excluded. Elimination of inappropriate shocks is to “first, do no harm.”